A Microflow Chip Technique for Monitoring Platelets in Late Pregnancy: A Possible Risk Factor for Thrombosis - He C; Ma H; Zhang T; Liu Y; Zhang C; Deng S (Journal of Blood Medicine)
Cui He,1 Haidong Ma,2 Tingting Zhang,1 Yu Liu,1 Cuiying Zhang,3 Surong Deng1 1Department of Blood Transfusion of Yong-chuan Hospital, Chongqing Medical University, Chongqing, 402160, People’s Republic of China; 2Department of Pharmacy of Yong-chuan Hospital, Chongqing Medical University, Chongqing, 402160, People’s Republic of China; 3Department of Obstetrics and Gynaecology of Yong-chuan Hospital, Chongqing Medical University, Chongqing, 402160, People’s Republic of ChinaCorrespondence: Surong Deng, Email 172346252@qq.comPurpose: To study the platelet adhesion and aggregation behaviour of late pregnancy women under arterial shear rate using microfluidic chip technology and evaluate the risk of thrombosis in late pregnancy.Methods: We included pregnant women who were registered in the obstetrics department of our hospital between January 2021 and October 2022 and underwent regular prenatal examinations. Blood samples were collected at 32– 35 weeks of gestation for routine blood tests and progesterone, oestradiol, and platelet aggregation function. A microfluidic chip was used to construct an in vitro stenosis vascular model to explore the platelet reactivity at shear rates of 1000s-1, 1500s-1 and 4000s-1. Flow cytometry was used to analyse the effect of shear rate induction on the expression of platelet membrane surface fibrin receptor (PAC-1) and P-selectin (CD62P) in pregnant women.Results: Compared to the non-pregnant healthy control group, the white blood cell count increased and platelet count decreased significantly in late pregnant women (P < 0.05), and platelet reactivity to agonists increased under non-flow conditions (adhesion and aggregation rates, P < 0.05). Microfluidic chip technology showed that platelet aggregation in late pregnant women increased significantly (P < 0.05) in the shear-rate environment and was positively correlated with the shear rate. The degree of aggregation at 4000s− 1 was more evident, but the stability of platelet aggregates was low. Shear rate increased PAC-1 and CD62P expression.Conclusion: Microfluidic chip technology was used to analyse the platelet aggregation function under arterial shear rate combined with flow cytometry to detect platelet activation, which was consistent with the traditional non-flow conditions used to evaluate platelet function. However, microfluidic technology can simulate a more realistic in vivo shear rate environment, providing more effective clinical application data and a theoretical basis for the diagnosis and prevention of platelet dysfunction and thrombotic diseases during pregnancy.Keywords: microfluidic chip, late pregnancy, platelets, adhesion aggregation, thrombosis